2024
DOI: 10.1002/advs.202400676
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma LINC01116 Outcompetes T Cells for Linoleic Acid and Accelerates Tumor Progression

Kun Ma,
Junhui Chu,
Yufeng Liu
et al.

Abstract: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer with a highly immunosuppressive tumor microenvironment and a typical pattern of disturbances in hepatic lipid metabolism. Long non‐coding RNAs are shown to play an important role in the regulation of gene expression, but much remains unknown between tumor microenvironment and lipid metabolism as a bridging molecule. Here, long intergenic nonprotein coding RNA 01116 (LINC01116) acts as this molecular which is frequently upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…[41] FABP5, another pivotal FABP mediating FA transport, was found not only to modulate the IL6/STAT3/VEGFA pathway in HCC cells, but also to regulate the tube formation, viability, and migration of human umbilical vein endothelial cells, indicating a potential angiogenic role of FABP5 in HCC. [42] Moreover, Ma et al [43] demonstrated that long intergenic noncoding RNA 01116 (LINC01116) blocks the ubiquitin-proteasome pathway to stabilize EWS RNA-binding protein 1 (EWSR1). Subsequently, EWSR1 acts as an m6A reader to regulate the stability of peroxisome proliferator-activated receptor-α (PPARα), increasing the expression of FABP1 to enhance FA intake, which facilitates the metastasis and growth of HCC.…”
Section: Lipid Intake and Ef Uxmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] FABP5, another pivotal FABP mediating FA transport, was found not only to modulate the IL6/STAT3/VEGFA pathway in HCC cells, but also to regulate the tube formation, viability, and migration of human umbilical vein endothelial cells, indicating a potential angiogenic role of FABP5 in HCC. [42] Moreover, Ma et al [43] demonstrated that long intergenic noncoding RNA 01116 (LINC01116) blocks the ubiquitin-proteasome pathway to stabilize EWS RNA-binding protein 1 (EWSR1). Subsequently, EWSR1 acts as an m6A reader to regulate the stability of peroxisome proliferator-activated receptor-α (PPARα), increasing the expression of FABP1 to enhance FA intake, which facilitates the metastasis and growth of HCC.…”
Section: Lipid Intake and Ef Uxmentioning
confidence: 99%
“…Antisense oligonucleotides targeting LINC01116 improved the curative effect of anti-PD-1 therapy in a mouse model, regulating antitumor immunity and inducing tumor regression of HCC. [43] Simvastatin, an inhibitor of cholesterol synthesis, intensifies the efficacy of PD-L1 antibodies to synergistically resist HCC metastasis and proliferation when applied via LSEC-targeted nano-delivery. [114] ICIs and mTKIs are most momentous drugs of systemic therapy.…”
Section: Influence Of Lipid Metabolic Reprogramming On the Efficacy O...mentioning
confidence: 99%